(untitled) (ModaPalavra e-periódico, 2018)
This paper presents the possibilities of applying digital manufacturing technologies for Surface Design in fashion products, demonstrating how these technologies may contribute to the user’s involvement in creation and production processes. More specifically, the focus of this article is on the uses of digital manufacturing for product personalization and for personal fabrication in a context of distributed production. The research method adopted is systematic and unsystematic bibliographic review. We consulted three databases and seven national journals repositories, as well as books, articles published in conference proceedings, specialized websites, and blogs. Therefore, the article presents some examples of digital manufacturing technologies application in fashion products Surface Design, discussing the possibilities and limitations of current technologies for the promotion of a distributed production scenario.